2023
DOI: 10.3390/pharmaceutics15010244
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanoparticle-Based Treatment and Imaging Modalities

Abstract: Over the last twenty years, nanomaterials have been widely used in cancer research [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Additionally, the nanocarriers allowed for sustained release of the drugs, ensuring a prolonged and controlled treatment. 161 The nanocarrier is composed of compounds such as lipids or polymers, which are biocompatible and can easily penetrate the ectopic pregnancy tissue. The researchers also noted that the nanocarriers enhanced the stability of the drugs, preventing their degradation and increasing their bioavailability at the target site.…”
Section: Innovative Nanomedicine In Ectopic Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the nanocarriers allowed for sustained release of the drugs, ensuring a prolonged and controlled treatment. 161 The nanocarrier is composed of compounds such as lipids or polymers, which are biocompatible and can easily penetrate the ectopic pregnancy tissue. The researchers also noted that the nanocarriers enhanced the stability of the drugs, preventing their degradation and increasing their bioavailability at the target site.…”
Section: Innovative Nanomedicine In Ectopic Pregnancymentioning
confidence: 99%
“…They found that this approach significantly improved the therapeutic efficacy of these drugs while minimizing their systemic side effects. Additionally, the nanocarriers allowed for sustained release of the drugs, ensuring a prolonged and controlled treatment . The nanocarrier is composed of compounds such as lipids or polymers, which are biocompatible and can easily penetrate the ectopic pregnancy tissue.…”
Section: Applications Of Nanotechnology-mediated Drug Delivery System...mentioning
confidence: 99%
“…Additionally, when given intravenously, MTX coupled with dendrimer nanoparticles has demonstrated encouraging outcomes for targeted delivery to inflammatory joints [62]. In addition to the studies using gold and dendrimer nanoparticles as carriers for the treatment of rheumatoid arthritis mentioned above, the simultaneous delivery of hydrophilic and hydrophobic drugs for the treatment of rheumatoid arthritis has also been investigated using chitosan/cyclodextrin nanoparticles [63]. Since gold nanoparticles are more effective and secure than traditional gold drugs, researchers are looking at using them as a delivery technique for RA therapy, particularly in the field of chrysotheraphy [64].…”
Section: Nano-particles As Carriers For Ros Regulation Therapiesmentioning
confidence: 99%
“…Since gold nanoparticles are more effective and secure than traditional gold drugs, researchers are looking at using them as a delivery technique for RA therapy, particularly in the field of chrysotheraphy [64]. According to these results, encapsulated nanoparticle carriers have considerable promise for enhancing the effectiveness and security of RA therapy [63].…”
Section: Nano-particles As Carriers For Ros Regulation Therapiesmentioning
confidence: 99%